Genome-wide analysis of Atlantic salmon (Salmo salar) mucin genes and their role as biomarkers - Sveen, Lene Rydal; Grammes, Fabian Thomas; Ytteborg, Elisabeth; Takle, Harald Rune; Jørgensen, Sven Martin (PLOS ONE, 2017)
The aim of this study was to identify potential mucin genes in the Atlantic salmon genome and evaluate tissue-specific distribution and transcriptional regulation in response to aquaculture- relevant stress conditions in post-smolts. Seven secreted gel-forming mucin genes were identified based on several layers of evidence; annotation, transcription, phylogeny and domain structure. Two genes were annotated as muc2 and five genes as muc5. The muc2 genes were predominantly transcribed in the intestinal region while the different genes in the muc5 family were mainly transcribed in either skin, gill or pyloric caeca. In order to investigate transcriptional regulation of mucins during stress conditions, two controlled experiments were conducted. In the first experiment, handling stress induced mucin transcription in the gill, while transcription decreased in the skin and intestine. In the second experiment, long term intensive rearing conditions (fish biomass ~125 kg/m3) interrupted by additional confinement led to increased transcription of mucin genes in the skin at one, seven and fourteen days post-confinement. publishedVersion